1995
DOI: 10.1097/00003246-199506000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival after intensive care unit admission with sepsis

Abstract: The most critical period for surveillance of bacteremic patients was in months 2 through 6 after discharge, during which time, the percentage of patients surviving decreased dramatically. The degree of physiologic derangement, as measured by the Acute Physiology Score, was a useful measure of prognosis within the first month after the score was assessed at ICU admission. However, beyond this period, prognostic utility decreased significantly. Healthcare providers should use caution concerning the expected surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
2
12

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(79 citation statements)
references
References 48 publications
3
62
2
12
Order By: Relevance
“…95,[102][103][104] Two further studies were also identified in the hand search of relevant journals 74,105 and three studies [106][107][108] were identified from the reference lists of the included studies. The flow chart of studies included in the review is reported in Figure 38.…”
Section: Studies Included In the Systematic Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…95,[102][103][104] Two further studies were also identified in the hand search of relevant journals 74,105 and three studies [106][107][108] were identified from the reference lists of the included studies. The flow chart of studies included in the review is reported in Figure 38.…”
Section: Studies Included In the Systematic Reviewmentioning
confidence: 99%
“…The flow chart of studies included in the review is reported in Figure 38. Ten individual publications 74,93,95,102,103,[105][106][107][108][109] were identified from nine separate studies (with two publications coming from the same study).…”
Section: Studies Included In the Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The morbidity in ICU for septic patients is 10% [29], while the fatality rate of SAE is as high as 51.0-72.0% [30]. However, SAE as one of the rare cause of initial central AVS has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of occurrence is high, with over 1665 cases of sepsis occurring yearly in the United States, reaching a lethality rate of 20-50 percent [8]. It is also important to note that, even with ideal treatment, the possibility of death is approximately 40 percent and can be greater than 50 percent in the most severe cases [9][10][11][12].…”
Section: Properties Of the Cytokinesmentioning
confidence: 99%